Sunk Cost Dilemma Behavior: The Contribution Marketing Expenses towards Financial Performance - Gesti Memarista; Lila Gestanti (Jurnal Keuangan dan Perbankan, 2018)
Marketing expenses can drove the financial performance of a company, but sometimes it was only a sunk cost. The sunk cost dilemma behavior can confuse a financial manager, confounding decisions about whether to invest in marketing. Thus, this study aimed to explain the relationship between marketing expenses and profitability. The research subjects were manufacturing firms listed on the Indonesia Stock Exchange between 2012 and 2016. The results showed that marketing-related research and development expenses, selling expenses, and operating cash flow had a significant positive relationship with return on assets (ROA) and return on equity (ROE). Moreover, lagged research and development expenses—specifically, expenses from the previous four years (RnDt-4)—had a significant effect on ROA and ROE. Leverage had a significant negative effect on ROA and ROE. On the other hand, firm size had no significant impact on profitability. The findings showed that marketing expenses were not a sunk cost; they were an investment that leads to good financial performance. Greater investments in marketing expected to entice consumers bought a company’s products and created more profitability, leading to improved financial performance.JEL Classifications: L25, M31, M37 DOI: https://doi.org/10.26905/jkdp.v22i4.1871